The aspects of the transdisciplinary cooperation in the training of the specialists in the field of Information Technologies - Butrimienė, Edita; Statkevičienė, Vida; Marčiulynienė, Rita (Lietuvos matematikos rinkinys, 2023)
In the article there is analyzed if the transdisciplinary cooperation influences the students’ learning results, and if such cooperation serves for the training of a specialist, who could work in a new environment of knowledge society that motivates a project work in continually variable commands. There is discussed a 3 year-experience of the application of the transdisciplinary cooperation in the training of students in the faculty of information science at Vytautas Magnus University and at Kaunas Institute of Arts, VAA (Vilnius Academy of Fine Arts). There are also investigated some research results of the transdisciplinary cooperation in training as well as the assessment of the students on their own.
Keywords: transdisciplinary learning; group learning